2014
DOI: 10.1002/cncy.21442
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 4 and microRNA 21 inverse expression is maintained in cells and exosomes from ovarian serous carcinoma effusions

Abstract: Ovarian serous carcinoma (OSC) is a fatal gynecologic malignancy usually presenting with bilateral localization and malignant peritoneal effusion. Programmed cell death 4 (PDCD4) is a tumor suppressor gene whose expression is directly controlled by microRNA-21 (miR-21). Exosomes are small cell-derived vesicles that participate in intercellular communication, delivering their cargo of molecules to specific cells. Exosomes are involved in several physiological and pathological processes including oncogenesis, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 35 publications
1
68
0
1
Order By: Relevance
“…microRNA 21, also known as hsamir-21 or miRNA 21 is encoded by the miR-21 gene located on chromosome 17q23.2 immediately downstream of the vacuole membrane protein-1 (VMP1) gene [4,6]. miR-21 is a common microRNA that is upregulated in a wide variety of cancers, including breast [13] ovaries [14] cervix [15] colon [16] lung [17] and liver [18]. In addition, it has been identified that miR-21 is consistently upregulated in several types of human cancers, including the stomach, as compared with matching non-cancerous tissue [19].miR-21 is also an oncogenic miRNA that can modulate the expression of multiple tumour suppressor genes, such as phosphatase and tensin homolog (PTEN), Serpini1, and programmed cell death 4 protein (PDCD4) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…microRNA 21, also known as hsamir-21 or miRNA 21 is encoded by the miR-21 gene located on chromosome 17q23.2 immediately downstream of the vacuole membrane protein-1 (VMP1) gene [4,6]. miR-21 is a common microRNA that is upregulated in a wide variety of cancers, including breast [13] ovaries [14] cervix [15] colon [16] lung [17] and liver [18]. In addition, it has been identified that miR-21 is consistently upregulated in several types of human cancers, including the stomach, as compared with matching non-cancerous tissue [19].miR-21 is also an oncogenic miRNA that can modulate the expression of multiple tumour suppressor genes, such as phosphatase and tensin homolog (PTEN), Serpini1, and programmed cell death 4 protein (PDCD4) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since there was a risk of consuming the whole of the specimen available, no further sections were obtained in two cases (one VSCC and one conventional SCC) to comply with the institute's ethical regulations on research conducted on human tissues. Staining was done automatically (BondmaX, Menarini, Florence, Italy) as described elsewhere,22 23 using the Bond Polymer Refine Detection kit (Leica Microsystem, Wetzlar, Germany), with rabbit polyclonal anti-SOCS-1 antibody (Santa Cruz Biotechnology, Santa Cruz, California, USA; working dilution 1:20, citrate buffer). Sections were then slightly counterstained with haematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…The demonstrated association between miRNA and their targets has most frequently been negative [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], as summarized in Table 2. Notably, the association between miRNAs and their targets is not always straightforward, which is demonstrated by the little overlap between predicted and experimentally shown targets [56].…”
Section: Mirnas and Their Predicted Targetsmentioning
confidence: 99%